2015
DOI: 10.1098/rsta.2014.0132
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural mechanisms of cyclic deformation, fatigue crack initiation and early crack growth

Abstract: In this survey, the origin of fatigue crack initiation and damage evolution in different metallic materials is discussed with emphasis on the responsible microstructural mechanisms. After a historical introduction, the stages of cyclic deformation which precede the onset of fatigue damage are reviewed. Different types of cyclic slip irreversibilities in the bulk that eventually lead to the initiation of fatigue cracks are discussed. Examples of trans- and intercrystalline fatigue damage evolution in the low cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
79
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 59 publications
2
79
0
2
Order By: Relevance
“…The crack is observed to initiate at the location corresponding to minimum equivalent plastic strain for both loads; however, both traction and effective triaxiality are high in the location of initiation as discussed in relation to Figure A,B. Higher plastic strains at the notch root where the triaxiality is low induce formation of extrusion/intrusion due to shearing along persistent slip bands . These effects have not been incorporated in the present model, as here the plane of the fatigue crack is assumed to be normal to the maximum opening stress direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crack is observed to initiate at the location corresponding to minimum equivalent plastic strain for both loads; however, both traction and effective triaxiality are high in the location of initiation as discussed in relation to Figure A,B. Higher plastic strains at the notch root where the triaxiality is low induce formation of extrusion/intrusion due to shearing along persistent slip bands . These effects have not been incorporated in the present model, as here the plane of the fatigue crack is assumed to be normal to the maximum opening stress direction.…”
Section: Resultsmentioning
confidence: 99%
“…To gain an insight into the physical significance of the length scale, that is the distance from the notch root to the location of maximum roughness, surface profile data in this region is first examined in further detail. Subsequently, the observations are compared with those obtained by SEM‐based interpretations of the fracture surface by earlier investigations …”
Section: Resultsmentioning
confidence: 99%
“…In steels under high cycle fatigue (HCF) or very high cycle fatigue (VHCF) loading, crack initiation accounts for a significant portion of fatigue life . Extensive studies have been conducted investigating the fatigue mechanisms for various steels, including ferritic steels, austenitic steels, and duplex steels . For the bearing steels, Lu et al demonstrated three kinds of failure modes of a bearing steel during fatigue tests and attributed the scatter in fatigue life to the scatter in the inclusion size.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fatigue is the major cause of failure in metallic structures [1][2][3] . The damage process of a metal under cyclic loading is generally decomposed into different steps 4,5) : cyclic hardening/softening, crack nucleation, small and short crack growth, long crack propagation andnal failure. The rst three steps are often referred as stage I and can represent up to 90% of the fatigue life in high-cycle fatigue (HCF) regime 6) .…”
Section: Introductionmentioning
confidence: 99%